Role of educational interventions related to occupational risks for nursing professionals (Research, Society and Development, 2021)
Objective: To describe the occupational risks found in the nursing work environment according to the literature, as well as to identify the role of educational health interventions related to occupational risks. Method: integrative review, who see ligibility criteria of the articles were correspond to the associated descriptors: Nursing Professionals, Biomedical Technology, Occupational Risks, Occupational Nursing and being available electronically in the following databases: VHL, LILACS, Medline/PUBMED, SCIELO and BDENF, with year of publication for 2015 to 2020.Results: 16 publications were selected for analysis, there was a predominance of Brazilian nursing authors, of which the nurse professional's concern was observed regarding ther eduction and control of occupational risks to his team in different work environments, and studies were found mostly in hospitals followed by basic health units, using continuing and permanent education as a tool to minimize occupational risks. Final Considerations: the nursing professional composing the health team is the professional most exposed to occupational risks in the various environments of health service provision. Risks such as biological, chemical, physical, ergonomic and psychosocial.